Challenges of engineering a functional growth plate in vitro - Zhang, Gangyu; Moya, Adrien; Scherberich, Arnaud; Martin, Ivan (Frontiers in Bioengineering and Biotechnology, 2025)
Several cartilage and bone organoids have been developed in vitro and in vivo using adult mesenchymal stromal/stem cells (MSCs) or pluripotent stem cells (PSCs) to mimic different phases of endochondral ossification (ECO), as one of the main processes driving skeletal development and growth. While cellular and molecular features of growth plate-like structures have been observed through the generation and in vivo implantation of hypertrophic cartilage tissues, no functional analogue or model of the growth plate has yet been engineered. Herein, after a brief introduction about the growth plate architecture and function, we summarize the recent progress in dissecting the biology of the growth plate and indicate the knowledge gaps to better understand the mechanisms of its development and maintenance. We then discuss how this knowledge could be integrated with state-of-art bioengineering approaches to generate a functional in vitro growth plate model.